Bankart Lesion: A Case Study of Evidence-Based Post-Operative Physiotherapy Management - Ashna Ravi; J Saravanan; Rani N Kavitha (Journal of Clinical and Biomedical Sciences)
Objective: To present an evidence- based post-operative physiotherapy management of Bankart lesion. Clinical Features: A 21-year-old male with a right shoulder Bankart lesion underwent corrective surgery after three years. Four weeks of intensive physiotherapy was initiated to restore shoulder function and improve his quality of life. Intervention and Outcome: Management included pain relief therapy and a progressive rehabilitation program focused on restoring range of motion, strengthening dynamic stabilizers, and improving shoulder proprioception. Four weeks post-operative physiotherapy, the patient regained full range of motion and strength comparable to the unaffected limb and was able to perform all daily functional activities. Conclusion: The case study on evidence-based postoperative physiotherapy management for Bankart lesions demonstrated substantial improvements in shoulder range of motion, muscle strength, and functional activity. Keywords Bankart Lesion, Post Physiotherapy Management, Rehabilitation